Relational Diagrams in Text Analysis - Boettcher, R.J. (Liber Annuus, 2006)
Abstract Analysis of texts requires the categorization, ordering and representation of large amounts of inter-relating data: word meaning, grammatical structure, semantics, and others. Some methods of diagramming the structure of a phrase have already been developed, with various levels of utility. However, the typical topology displays only a single scenario, constraining the reader to a single value at each point of multivalence. Thus to list N possibilities requires N such diagrams, which becomes impractical for anything but the most simple phrase. In contrast, the present survey applies a network topology, which allows the freedom of representing multivalence and ambiguity, external referents and engagements.